DEVELOPMENT OF LEARNING ACHIEVEMENT AND ANALYTICAL THINKING ABILITY IN THE LEARNING AREA OF SCIENCE AND TECHNOLOGY ON THE TOPIC OF WEATHER USING THE 5E INQUIRY-BASED LEARNING MODEL COMBINED WITH GRAPHIC ORGANIZERS FOR GRADE 5 STUDENTS AT BANNATHOM SCHOOL - Tiyajan, Kamonpat; Rotchu, Phananoi; Kadroon, Thanya (Journal of MCU Nakhondhat, 2026)
The purposes of this research were to: 1) Develop 5E inquiry-based learning lesson plans combined with graphic organizers on the topic of Weather in the learning area of Science and Technology to meet the efficiency criterion of 80/80 and an effectiveness index greater than 0.50; 2) Compare students’ learning achievement before and after learning; 3) Compare students’ analytical thinking ability before and after learning; and 4) Investigate students’ satisfaction toward the 5E inquiry-based learning combined with graphic organizers. This study employed an experimental research design using a one-group pretest–posttest design. The sample consisted of 14 Grade 5 students from Bannathom School during the first semester of the 2024 academic year, selected through purposive sampling. The research instruments included: 1) Lesson plans, 2) A learning achievement test, 3) An analytical thinking ability test, and 4) A satisfaction questionnaire. Data were analyzed using percentage, mean (), standard deviation (S.D.), and t-test. The results revealed that: (1) The developed lesson plans had an efficiency of 81.95/82.62, which was higher than the 80/80 criterion, and an effectiveness index of 0.72 (72.45%); 2) Students’ posttest learning achievement ( = 24.79, S.D.=3.58) was significantly higher than their pretest achievement ( = 11.07, S.D.=2.09) at the .05 level; 3) Students’ posttest analytical thinking ability ( =12.07, S.D.=1.86) was significantly higher than their pretest ability ( = 5.64, S.D.=1.34) at the .05 level; and (4) The overall level of satisfaction of the Grade 5 students toward the 5E inquiry-based learning combined with graphic organizers was at a high level ( =4.48, S.D.=0.49). These findings can be used as a guideline for developing students’ analytical thinking ability.